Multi-technique characterization of TiO2 nanoparticles: Crystallite size, microstrain, and phase analysis for nanomaterial applications – a review - Sukarman; Budi Kristiawan; Eko Prasetya Budiana; Khoirudin; Amri Abdulah (Hybrid Advances, 2025)
This review reports the structural characterization of titanium dioxide nanomaterials and their composites, which are widely applied in catalysis, coatings, and thermal systems. A consistent dimensional hierarchy has been reported across studies: crystallite size (X-ray diffraction) < grain size (transmission electron microscopy) < particle size (scanning electron microscopy or dynamic light scattering). The deviations between these dimensions ranged from ∼3 % to >130 % depending on the synthesis temperature, agglomeration, and instrumental resolution. Crystallite sizes as low as 2.12 nm have been reported, whereas the corresponding grain sizes typically exceed 20 nm. The microstrain values derived from the Williamson–Hall, uniform deformation, and Warren–Averbach models ranged from 0.06 % to 1.14 %, indicating variable lattice distortion. The dislocation density values ranged from 0.0389 to 0.224 × 1016 m−2, often correlating inversely with the crystallite size. The phase compositions confirmed by Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy included anatase, rutile, and iron oxide phases. ζ-potential and dynamic light scattering analyses consistently revealed colloidal stability and aggregation. These findings highlight the limitations of single-technique characterizations and support integrated multi-method approaches alongside artificial intelligence-based calibration for reliable structure–property optimization in titanium dioxide nanomaterials.